VULNERABLE GROUPS: THE COMPLEXITY INVOLVED IN THE POLICE APPROACH - Tiego Gomes de Oliveira, Paulo; Malta de Oliveira, Francisco; Luiz Teixeira, Thiago (Revista Gênero e Interdisciplinaridade, 2025)
The study aims to analyze the police assistance provided to the LGBTQI+ population in police approaches. Through diversified bibliographical research, after contextualization and presentation of terms and concepts, the importance of establishing, in the State of Minas Gerais, a care protocol that involves and respects the specificities of this social group is presented. The activity of the Military Police must meet the principle of human dignity and, certainly, the enhancement of public safety, through the promotion of social well-being and the free exercise of citizenship. As a result of the study, it is important to note the importance and urgency of applying normative instructions that guide police action towards the LGBTQI+ public, enabling ethical and excellent service, which contributes to the eradication of discriminatory behavior and the revictimization of this portion. of the mining population.